2014
DOI: 10.2217/hep.13.21
|View full text |Cite
|
Sign up to set email alerts
|

Current role of transarterial chemoembolization and radioembolization in the treatment of metastatic colorectal cancer

Abstract: In this article, we review two liver-directed therapies that are currently used for the palliative treatment of primary and secondary hepatic malignancies, transcatheter arterial chemoembolization (TACE), including a new type of TACE with drug-eluting beads, and radioembolization. Important developments and administration techniques for all therapies are discussed, as well as their integration into the current routine clinical care for management of metastatic colorectal cancer. According to published data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Transcatheter liver-directed therapies (LDTs) have been proven to increase survival in patients with hepatocellular carcinoma, cholangiocarcinoma, as well as colorectal cancer (CRC) and neuroendocrine tumors with liver-dominant metastases [ 28 , 29 , 30 , 31 ]. However, there are very few studies describing the efficacy and safety of LDTs in patients with primary or metastatic hepatic sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter liver-directed therapies (LDTs) have been proven to increase survival in patients with hepatocellular carcinoma, cholangiocarcinoma, as well as colorectal cancer (CRC) and neuroendocrine tumors with liver-dominant metastases [ 28 , 29 , 30 , 31 ]. However, there are very few studies describing the efficacy and safety of LDTs in patients with primary or metastatic hepatic sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…SIR-Spheres are resin-based, while TheraSpheres are glass-based. Compared with other transarterial therapies, considerably more prospective data are available for this treatment modality [114][115][116][117][118]. In a Phase II trial, Cosimelli et al examined the effects of TARE on CRLM.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Using RECIST criteria, 1 (2%) patient had a complete response, 11 (22%) had a partial response, 12 (24%) had stable disease, 22 (44%) had progressive disease and 4 (8%) were nonevaluable. Other studies have demonstrated the promising role of TARE, particularly in the patient population refractory to systemic chemotherapy [115,119,120]. Indeed, just as with TACE, more data are required to make appropriate recommendations for the application of TARE in CRLM.…”
Section: Radiation Therapymentioning
confidence: 99%